(untitled) (Research, Society and Development, 2022)
Objective: This study aimed to compare the functional mobility and postural balance of older adults among smild and moderate stages of Alzheimer’s disease using the Timed Up and Go test (TUGT) and the Clinical Test of Sensory Interaction and Balance (CTSIB). Methodology: Forty elderly people were divided into two groups according to the mild (CDR1; n = 26) and moderate (CDR2; n = 14) stages of the disease. The Clinical Dementia Rating Scale (CDR) was used for staging the disease, which allows classifying the different degrees of dementia, assessing cognition and behavior. The scale allows classification into CDR 0 (normal or no alteration); 0.5 (questionable or mild cognitive impairment); 1 (mild dementia); 2 (moderate dementia) and 3 (severe dementia). In this study, only subjects classified as CDR 1 or CDR 2 were included. For the assessment of functional mobility, the Timed Up and Go Test (TUGT) was used in the conditions of single task, dual cognitive task and dual motor task, and the Clinical Test of Sensory (CTSIB) to assess postural balance. Data were compared between groups. Results: Performance on the TUGT single task, cognitive dual task, and motor dual task was significantly worse in the CDR2 group compared to the CDR1 group (p < 0.05). The CTSIB was not significantly different between the groups in the four conditions. Conclusion: Functional mobility during tasks involving cognition differs between older adults with mild and moderate dementia, and this commitment is more accentuated in dual-task situations. Postural balance did not differ between the stages of the disease.